2013
DOI: 10.1016/j.bbrc.2013.09.042
|View full text |Cite
|
Sign up to set email alerts
|

RSK2-induced stress tolerance enhances cell survival signals mediated by inhibition of GSK3β activity

Abstract: Our previous studies demonstrated that RSK2 plays a key role in cell proliferation and transformation induced by tumor promoters such as epidermal growth factor (EGF) in mouse and human skin cells. However, no direct evidence has been found regarding the relationship of RSK2 and cell survival. In this study, we found that RSK2 interacted and phosphorylated GSK3β at Ser9. Notably, GSK3β phosphorylation at Ser9 was suppressed in RSK2(-/-) MEFs compared with RSK2(+/+) MEFs by stimulation of EGF and calcium ionoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…RSK2 is a member of the RSK family and is phosphorylated at the C-terminal kinase and linker domains by ERK1/2 [ 8 ] and at the N-terminal kinase domain by phosphoinositide-dependent kinase 1 (PDK1) [ 9 ]. Activated RSK2 transduces its activation signal to various downstream target proteins including transcription and epigenetic factors [ 10 12 ], kinases [ 13 ], and scaffolding proteins such as nuclear factor of κ light polypeptide gene enhancer in B-cells inhibitor α (IκBα) [ 14 ], and regulates diverse cellular activities involved in cell proliferation, transformation and motility [ 15 ]. For instance, our previous results have demonstrated that the enhanced cAMP-dependent transcription factor 1 (ATF1) activity, caused by the epidermal growth factor (EGF)-mediated Ras/ERKs/RSK2 signaling pathway, induces cell proliferation and transformation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RSK2 is a member of the RSK family and is phosphorylated at the C-terminal kinase and linker domains by ERK1/2 [ 8 ] and at the N-terminal kinase domain by phosphoinositide-dependent kinase 1 (PDK1) [ 9 ]. Activated RSK2 transduces its activation signal to various downstream target proteins including transcription and epigenetic factors [ 10 12 ], kinases [ 13 ], and scaffolding proteins such as nuclear factor of κ light polypeptide gene enhancer in B-cells inhibitor α (IκBα) [ 14 ], and regulates diverse cellular activities involved in cell proliferation, transformation and motility [ 15 ]. For instance, our previous results have demonstrated that the enhanced cAMP-dependent transcription factor 1 (ATF1) activity, caused by the epidermal growth factor (EGF)-mediated Ras/ERKs/RSK2 signaling pathway, induces cell proliferation and transformation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, our previous results have demonstrated that the enhanced cAMP-dependent transcription factor 1 (ATF1) activity, caused by the epidermal growth factor (EGF)-mediated Ras/ERKs/RSK2 signaling pathway, induces cell proliferation and transformation [ 16 ]. The increased NF-κB transactivation activity, resulting from the RSK2-IκBα signaling pathway, modulates cell survival induced by the FAS-mediated death signaling pathway [ 13 ]. A recent report demonstrates that RSK2 promotes the invasion and metastasis of head and neck squamous cell carcinoma cells in humans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the accumulation of β‐catenin has been demonstrated to promote the development of multiple cancers, GSK3β was thought to act as a tumor suppressor by controlling the level of β‐catenin. Several studies have reported the anti‐tumorigenesis role of GSK3β using gain‐ and loss‐of‐function approaches in different tumors such as breast and skin tumors . Moreover, GSK3β overexpression has been reported to affect the viability of cancer cells by enhancing the degradation of pro‐tumorigenesis factors such as Cdc25A and c‐Myc .…”
Section: Discussionmentioning
confidence: 99%
“…| 2313 by controlling the level of β-catenin. Several studies have reported the anti-tumorigenesis role of GSK3β using gain-and loss-of-function approaches in different tumors such as breast and skin tumors 50,51.…”
mentioning
confidence: 99%